Sr‐O‐C isotope signatures reveal herbivore niche‐partitioning in a Cretaceous ecosystem. (14th March 2022) - Cullen, Thomas M.; Zhang, Shuangquan; Spencer, Joseph; Cousens, Brian
Abstract: Stable and radiogenic isotopes represent powerful tools for reconstructing ecological and environmental patterns in ancient ecosystems. The Cretaceous of North America preserves a diverse record of fossil vertebrates well‐suited to analysis using these proxies, contained within many well‐sampled and stratigraphically well‐characterized intervals. Multiple hypotheses have been offered to explain the diverse assemblages of megaherbivores that co‐occurred in the relatively restricted available landmass here, including various forms of niche‐partitioning related to habitat preference, dietary specialization and feeding height stratification. Here we analyse the 87 Sr/ 86 Sr, δ 13 C and δ 18 O of bioapatite samples obtained from a range of herbivores, faunivores and endemic taxa, from a spatiotemporally‐constrained and intensively‐sampled site in the upper Oldman Formation, to test if megaherbivores partitioned their niches based on spatial patterns of occupation and resource‐use. We also compare measured strontium values to regional 87 Sr/ 86 Sr data to assess biogeographical range sizes, habitat breadth and migration potential. We find that hadrosaurs had broad ranges, whereas ankylosaurs and ceratopsids were more spatially restricted. The 87 Sr/ 86 Sr ranges of hadrosaurs are much wider and do not overlap with those of other ornithischians, potentially related to dietary differences driven by a combination of feeding height‐stratification and habitat breadth differences. Ankylosaurs and ceratopsids overlapped extensively in 87 Sr/ 86 Sr, δ 13 C and δ 18 O, indicating overlap in the same habitats and intake of similar resources, and suggesting more complex spatiotemporal variation in resource‐use patterns, fine‐scale dietary differences, and/or sufficient resource‐availability to reduce the degree of competition given this theoretical niche overlap. Additional analyses integrating ecomorphological proxies may elucidate these patterns further.